Report on two deep-water caridean shrimp species (Crustacea: Decapoda: Caridea: Alvinocarididae, Acanthephyridae) from the northeastern South China Sea - Li, Xinzheng (Zootaxa, 2015)
Two deep-water species of caridean shrimps collected during recent dives by the Chinese manned submersible “Jiaolong” represents new records for the South China Sea: Alvinocaris longirostris Kikuchi & Ohta, 1995 (Alvinocarididae) and Acanthephyra faxoni Calman, 1939 (Acanthephyridae). Specimens of these two species were collected from Jiaolong Cold Seep I, off Guangdong Province, China (depth 1138 m). Alvinocaris longirostris is known to be associated with chemosynthetic community, whereas Acanthephyra faxoni is a bathypelagic inhabitant, of which the occurrence in seep site is merely opportunistic. An identification key to species of Alvinocaris is provided.